Mental Health Needs of Families of Patients in Intensive Care Units and the Role of Mobile Health: Survey Study - Faiola, Anthony; Soroya, Saira; Hao, Zhonglin; Munker, Reinhold (JMIR Formative Research, 2025)
BACKGROUND: The experiences of patients with COVID-19 and their families manifested the most devastating effects of family separation since the 1918 Spanish influenza pandemic and, with it, a call for solutions to patient isolation and its effect on family mental health. OBJECTIVE: This study examined the recent experiences of families of critical care (intensive care unit; ICU) patients related to anxiety and depression (AD), satisfaction with clinician-family communication, and counseling from mental health and social services. This study explored correlations between these factors and family interest in mobile health (mHealth) designed to improve information flow and communication from patient bedside to remote families. METHODS: Using a 36-question quantitative survey, we collected 97 responses over 6 months. We selected participants by using a convenience sampling strategy. To analyze data, we applied descriptive and inferential statistics. Participants represented a spectrum of ages, relationships to patients, and races (n=78, 80% White; n=17, 18% Black; n=2, 2% other races). Approximately 17% (n=16) of the patients were admitted for cancer, 13% (n=13) were admitted for COVID-19, and 21% (n=20) were admitted for other conditions. RESULTS: The mean score for remote families' satisfaction with patient health updates from the bedside and mental health services was 2.94 (SD 1.31), whereas that for phone communication was lower on average. The mean scores of family AD levels were elevated, and levels were higher among family members during the ICU stay than after discharge. These findings confirmed evidence of a negative correlation between transportation difficulties and satisfaction with the frequency of information provided (r=-0.284; P=.005), suggesting that, with the increase in transportation challenges, families become less satisfied with the frequency of patient health information. Family members expressed strong interest in using mHealth information and communication services (mean 8.34, SD 1.98) and having easy access to social workers to manage AD (mean 8.29, SD 2.03). Families experiencing higher levels of anxiety during patients' ICU stays had significantly greater interest in the use of an mHealth app that would provide direct access to social workers (r=0.326; P<.001), in using an mHealth videoconferencing app (r=0.319; P=.002), and in overall mHealth app use (r=0.322; P<.001). CONCLUSIONS: Family members experienced high levels of AD during patient ICU admission, as well as after discharge even though their mental health challenges were reduced. Families were highly dissatisfied with the frequency of health updates, with lower satisfaction reported among those who faced difficulties arranging transportation or lived further from the hospital. Modest but statistically significant correlations were observed between family members' reported mental health status during ICU stays and an interest in an mHealth app that could provide access to real-time bedside information, facilitate communication with bedside nurses, and support connections with social workers.
Keywords: Affect (linguistics); COVID-19; Depression (economics); Health care; ICU; Mental health; Mental illness; Receipt; communication; dept.ils; digital tools; eHealth; health equity; health technology; intensive care unit; mental health; mobile health

Investigating the Feasibility, Usability, and Efficacy of a Mobile App to Reduce Anxiety and Depression in Families of Critical Care Cancer Patients: A Quasi-Experimental Pilot Study - Faiola, Anthony; Soroya, Saira; Munker, Reinhold; Hao, Zhonglin; Lambert, Joshua (Healthcare, 2026)
Background: Cancer patients admitted to the bone marrow transplant (BMT) unit face life-threatening medical conditions. Consequently, their family members experience uncertainty, resulting in high levels of anxiety and depression (AD). Limited updates and communication from medical staff exacerbate these emotional burdens. To address these challenges, we developed a mobile health (mHealth) intervention, FamCarePlus, and evaluated its feasibility, usability, and efficacy. We hypothesized that the FamCarePlus application would demonstrate a high degree of feasibility and usability and would reduce AD compared to a control group relying solely on traditional communication through the nurses’ station. Methods: We employed a quasi-experimental pretest/posttest non-randomized, non-blinded self-report design over 3 weeks, with an experimental group (n = 10) using FamCarePlus and a control group (n = 9). We selected participants via convenience sampling using the electronic medical record to identify eligible patients and families, guided by inclusion and exclusion criteria. We used descriptive statistics and the Hospital Anxiety and Depression Scale (HADS) guidelines to analyze the data. Feasibility was defined by a retention rate > 80%, with usability testing using the System Usability Scale (SUS) and NASA Task Load Index (NASA-TLX) surveys. The HADS measured AD, comparing baseline to Week 3. Results: We met our feasibility criteria of >80%. All SUS and NASA scores were in the higher index, suggesting a significant degree of usability and low workload demand on participants. For efficacy, we compared baseline mean scores, with the experimental group reporting lower AD levels at Week 1 (41.9% and 27.8%, respectively) than the control group (55.2% and 34.2%, respectively). From Week 1 to Week 3, the percentage change showed an 8.6% decrease in anxiety in the experimental group, compared to a 12.8% decrease in anxiety in the control group. These results were consistent when analyzed according to HADS guidelines. Conclusions: The findings of this study provide preliminary evidence that the FamCarePlus intervention is feasible and usable, while also demonstrating that its use may be associated with a sustained reduction in AD levels among family members of patients admitted to the BMT unit. These outcomes underscore the potential of digital interventions to address disparities in patient health information access and psychosocial support.
Keywords: Anxiety; Depression (economics); Descriptive statistics; Hospital Anxiety and Depression Scale; System usability scale; Usability; Workload; anxiety; cancer; depression; dept.ils; families; intensive care unit; mHealth

Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-9175-8
Keywords: dept.ils

A Study of the Coverage of Open Educational Resources (OER) Through Websites of Colleges and Universities in Connecticut - Brown, Mary; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2025)
Notwithstanding reports of increased awareness and use of Open Educational Resources (OER) in higher education, the literature notes that awareness and use of and institutional support for OER remain major challenges to campuses seeking to reduce student cost burden and support access to materials. OER also support faculty who desire to move beyond the traditional textbooks in order to increase their students’ engagement and thereby access to learning, to support pedagogical changes they are making that enhance student learning, and to give faculty greater control over their courses. The university website, as a public-facing vehicle to aid students, parents, alumni, faculty, the community, and interested others in being aware, among other things, of the resources available, is examined for findable support for OER. The purpose of this study is to show, through examination of their websites, a snapshot of the response of Connecticut universities and colleges to OER. Through an examination of these websites, we gage the ability to connect with information related to OER through the university website.
Keywords: dept.ils

Artificial Intelligence, Misinformation, and Libraries: A New Frontier for Information Professionals - Salubi, Oghenere (Proceedings of the Association for Information Science and Technology, 2025)
Generative artificial intelligence (AI) has experienced rapid advancement, fundamentally transforming the information landscape. This technological shift has not only amplified the dissemination of misinformation but has also posed significant challenges to conventional frameworks of trust and verification. This paper explores the dual impact of AI: its potential to enhance information services while simultaneously amplifying misinformation and disinformation. Seven AI-generated misinformation cases between 2022 and 2025—ranging from deepfakes and political propaganda to impersonation and amplification were analyzed. Through thematic case analysis and interdisciplinary synthesis, the study proposes the AI-Misinformation Resilience Model (AIM-RM), a conceptual framework guiding proactive responses across verification infrastructure, digital literacy, and ethical policy engagement. Drawing on recent scholarly literature and grounded in information ethics, epistemic trust, and sociocultural literacy, the model offers a path forward for LIS professionals seeking to navigate the post-truth era. Annual Meeting of the Association for Information Science & Technology | Nov. 14 – 18, 2025 | Washington, DC, USA.
Keywords: Deepfakes; Generative artificial intelligence; Information literacy; Library and information professionals; Misinformation; dept.ils

Developing a Video Game Metadata Schema and Fillable Form Template for Accessible Interactive Media Cataloging in Public Libraries - Myers, Jason (Cataloging & Classification Quarterly, 2025)
Keywords: Cataloging; Computer science; Information retrieval; Metadata; Multimedia; Schema (genetic algorithms); Video game; World Wide Web; cataloging interactive media; dept.ils; fillable forms; metadata schema; public libraries; video games

Adopting Critical Cataloging Practices Post Diversity Audit: Connecting the Community to Your Collection - Anderson, Jessica K.; Liu, Yan Quan (Library Resources & Technical Services, 2025)
To increase patrons’ ability to find resources, it is imperative to investigate barriers and biases in thedescriptive catalog data for inclusive collection management and development standards. This studyused a specially designed descriptive approach to gather quantitative data from 101 public librariansin Connecticut via a Qualtrics survey to identify the key variables that influence the successfulenhancement of online public access catalog (OPAC) metadata after a diversity audit of the librarymaterials. The results revealed factors that promote or impede the integration of inclusive catalogingthat reflects the diversity of the community: (1) appreciating the benefits of audit methods that arefocused on bibliographic records, (2) recognizing the need for buy-in and participation from theentire organization, and (3) stressing the useful integration of institutional and community feedbackto improve the collection’s accessibility and representation. The findings provide practical adviceto public libraries that want to satisfy the diverse demands of their user base by integrating criticalcataloging frameworks into their diversity and inclusion objectives.
Keywords: SCSU-student; dept.ils

Digitization Practices in U.S. Urban Libraries: Tools, Technologies, and Metadata Standards - Torres, Natalia; Liu, Yan (Public Library Quarterly, 2025)
Keywords: Business; Computer science; Cultural heritage preservation; Data science; Digitization; Engineering; Library science; Metadata; SCSU-student; Telecommunications; World Wide Web; dept.ils; digital collections; digitization practices; online accessibility; urban libraries

Perceived awareness, benefits, and strategies of Pakistani editors regarding open-access journal publishing - Raza, Muhammad Zahid; Rafiq, Muhammad; Soroya, Saira Hanif (Global Knowledge, Memory and Communication, 2025)
This study aims to discover the perceived awareness, benefits and suitable strategies of the Pakistani editors of Higher Education Commission (HEC)-recognized scholarly journals regarding open-access (OA) journal publishing in Pakistan.,A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of 329 HEC-recognized journals in Pakistan.,The awareness level of the respondents of the Pakistani journals is low regarding the OA concepts, resources and initiatives. The respondents of OA journals have better awareness levels than the respondents of non-OA journals. All the respondents of journals are convinced and have the view that OA journals have wider benefits for the academic community, and they need to flourish. A majority of the respondents are of the view that HEC should sponsor financial resources and technical training for OA journal publishing. The respondents of OA journals are more in favor of supporting OA journal publishing than the respondents of non-OA journals.,This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals by using different research paradigms such as qualitative or pragmatic research approaches.,To the best of the authors’ knowledge, this study is the first comprehensive study on this phenomenon and is an effort to fill this gap and invigorate the scholarly literature. It may attract the attention of the policymakers, funding bodies, parent institutions of the journals and the HEC to cope with the low awareness level of the Pakistani editors regarding the OA concepts, resources and initiatives; and suitable strategies required to uplift the OA journal publishing paradigm in Pakistan.
Keywords: dept.ils; peer-reviewed

Perceptions of the Pakistani editors for open access journal publishing: a developing country’s perspective - Raza, Muhammad; Rafiq, Muhammad; Soroya, Saira (Information Development, 2025)
Objectives This study has been designed to determine Pakistani editors’ perceptions regarding the Open Access (OA) publishing practices of the Higher Education Commission (HEC)-recognized journals in Pakistan, and to assess their best OA publishing models. Methodology A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of all 329 HEC-recognized journals in Pakistan. Findings This study exposed that public and teaching institutes are leading in OA journal publishing in Pakistan as compared to private and research institutes. Diamond OA, and Gold OA publishing models are popular among the respondents; however, respondents are not convinced to follow any specific OA publishing model due to their different choices. A large majority (92%) of the journals belong to the Y category (the lowest) of journals. A large majority (72%) of the journals in Pakistan is adopting the Open Journal System (OJS), and parent institutions installed web browsers. CC-BY-NC and CC-BY licenses are their favorite licenses. Significance The present study is the first comprehensive study on editors’ perceptions for OA journal publishing and is an effort to fill this gap to invigorate the scholarly literature. This study may enable the journals, editors, and publishers to follow the best OA journal publishing practices of the Pakistani journals for global OA usage of scholarly journals. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, policy organizations, and parent institutions of journals.
Keywords: Computer science; Developing country; Economic growth; Economics; Library science; MEDLINE; Media studies; Open access journal; Open access publishing; Perception; Perspective (graphical); Political science; Psychology; Public relations; Publishing; Scopus; Sociology; dept.ils; peer-reviewed

Academic Integrity: Effects of Demographic Variables on Students’ Conduct - Soroya, Dr Muhammad Shahid; Hashmi, Dr Muhammad Amir; Soroya, Saira Hanif (South Asian Studies, 2020)
This study aimed to find out the effects of demographic variable i.e. gender, age, group of studies, GPA etc. on level of academic integrity among Pakistani students. The design of the study is quantitative in nature, in which the survey research method was employed to gather data from the respondents. A self-reported questionnaire was adapted on the basis of previously developed and validated questionnaire, with the consent of the authors. The developed scale was validated with the help of experts and pilot tested. Multilevel stratified convenience sampling technique was used to collect data from 4 provinces and federal area of Pakistan. The collected data was analyzed by using SPSS 16.0 version
Number: 2
Keywords: dept.ils

Embracing the metaverse: a survey of virtual reality and augmented reality practices at the United States’ top one hundred university libraries - Guo, Yajun; Li, Shuai; Zhang, Xindi; Fu, Yiyang; Yuan, Yiming; Liu, Yanquan (College & Research Libraries, 2024)
The purpose of this study is to learn more about virtual reality (VR) and augmented reality (AR) practices at the United States’ top one hundred university libraries, as well as how they are engaging with the metaverse. We conducted qualitative and descriptive analysis on the websites of the top one hundred university libraries in the United States to determine the application fields and application proportions of VR and AR technologies and found good practice examples of using VR and AR technologies in this field. The findings show that 86 percent of the top one hundred US university libraries have implemented VR and AR technologies, with practice areas focused on: VR/AR studio and VR/AR makerspace; immersive learning services and virtual exhibitions/conference services; visual geographic information system and VR navigation services; virtual reading services and visual retrieval services; and VR reference services. The study provides university library administrators and professionals with the most up-to-date information and best practices of VR and AR engagement areas and the proportion of use, which can aid in the development of strategies to leverage VR and AR technologies to improve patron service and embrace the metaverse for the communities they serve.
Number: 7
Keywords: Metaverse；Virtual reality；Augmented reality；University Library；America；Survey; dept.ils; peer-reviewed

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

Assessing the impact of health information orientation and health information literacy on patients’ engagement with health information - Hashmi, Ferhana Saeed; Soroya, Saira Hanif; Mahmood, Khalid (Journal of Information Science, 2024)
Health information engagement can help individuals to find and use reliable sources of health information to make informed decisions about their health. This helps to improve their health outcomes and prevent unnecessary healthcare costs. Drawing upon the cognitive behavioural theory, this pilot study postulated a model to understand that the consequences of information orientation in terms of information engagement (behaviour), information literacy (cognition) and information avoidance (behaviour) in post-COVID era under health context. Furthermore, the moderation effects of health information literacy (HIL) are also calculated in managing health information avoidance beahvior. This pilot study is conducted in the context of social media exposure to health information by diabetic patients in Pakistani community. The proposed model was tested using Partial Lease Square Structural Equational Modelling (PLS-SEM). The data were collected from 166 diabetic patients (active social media users) through a survey. The study findings suggest that health information orientation on social media leads to HIL and engagement. Whereas, it has significant negative impact towards health information avoidance behaviour. Furthermore, HIL significantly increases health information engagement of diabetic patients. Also, HIL moderates the relationship between health information orientation and information engagement positively, whereas between health information orientation and health information avoidance negatively.
Keywords: dept.ils; peer-reviewed

Surfing the World of Knowledge: Analytical Case Studies of Digital Liberties in the United States - Liu, Dr Yan Quan (Independently published, 2021)
This work compiles a database that provides analytical case studies of typical digital libraries as an enhancement for educating and learning to meet the needs of students, librarians, scholars, and those who are interested in this resource.
Keywords: dept.ils

A Study of the Deployment of Institutional Repositories in Colleges and Universities in Connecticut - Clarke, Christopher D.; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2023)
In the past several years, many colleges and universities have developed institutional repositories as a means of highlighting the research and scholarship conducted at their institution as well as a means of combating the current publication model. Past studies have concentrated on growth in the total number of repositories, but none has looked at how the number of repositories in a particular region compares to those institutions without a repository. The primary purposes of this study were to find out how many colleges and universities in Connecticut have developed institutional repositories and how they have used these institutional repositories. Overall, this study revealed that less than a third of the academic institutions in Connecticut have institutional repositories. These repositories are most frequently found in the state sponsored universities and the independent, nonprofit schools. On the other hand, none of the community colleges, which constitute one of the largest proportion of schools in the state behind independent, nonprofits, has a repository. A vast majority of the repositories are registered with OpenDOAR, and nearly all of them use Digital Commons as their platform. The two most popular types of content found in Connecticut institutional repositories are journal articles and theses & dissertations.
Number: 1
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
0 citations (Crossref) [2023-10-31] Number: 3
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

Services to mobile users: the best practice from the top-visited public libraries in the US - Liu, Yan Quan; Lewis, Sarah (Information Technology and Libraries, 2023)
Libraries are adapting to the changing times by providing mobile services. One hundred fifty-one libraries were chosen based on circulation, with at least one library or library system from each state, to explore the diverse services provided to mobile users across the United States. According to the data, mobile apps, mobile reference services, mobile library catalogs, and mobile printing are among public libraries’ most-frequently offered services, as determined by mobile visits, content analysis, and librarian survey responses. Every library examined had at least one mobile website, mobile catalog, mobile app, or webpage adapted for a mobile device. Following the COVID-19 outbreak, services such as mobile renewal, subscriber database access, mobile reservations, and the ability to interact with a librarian were expanded to allow better communication with customers—all from the comfort and safety of their own homes. Libraries are continually looking for innovative methods to assist their mobile customers as the world changes.
0 citations (Crossref) [2023-10-31] Number: 1
Keywords: Mobile Apps; Mobile services; Public Libraries; SCSU-student; Survey study; dept.ils; peer-reviewed

Contactless Services: A Survey of the Practices of Large Public Libraries in China - Guo, Y.; Yang, Z.; Yuan, Y.; Ma, H.; Liu, Y.Q. (Information Technology and Libraries, 2022)
Contactless services have become a common way for public libraries to provide services. As a result, the strategy used by public libraries in China will effectively stop the spread of epidemics caused by human touch and will serve as a model for other libraries throughout the world. The primary goal of this study is to gain a deeper understanding of the contactless service measures provided by large Chinese public libraries for users in the pandemic era, as well as the challenges and countermeasures for providing such services. The data for this study was obtained using a combination of website investigation, content analysis, and telephone interviews for an analytical survey study of 128 large public libraries in China. The study finds that touch-free information dissemination, remote resources use, no-touch interaction self-services, network services, online reference, and smart services without personal interactions are among the contactless services available in Chinese public libraries. Exploring the current state of contactless services in large public libraries in China will help to fill a need for empirical attention to contactless services in libraries and the public sector. Up-to-date information to assist libraries all over the world in improving their contactless services implementation and practices is provided. © 2022.
1 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Exploring library core competencies: A text mining study of american library association’s job advertisements from 2006 through 2017: - Yang, Qinghong; Shi, Zehong; Liu, Yan Quan (Social Science Computer Review, 2021)
Are core competency requirements for relevant positions in the library shifting? Applying natural language processing techniques to understand the current market demand for core competencies, this study explores job advertisements issued by the American Library Association (ALA) from 2006 to 2017. Research reveals that the job demand continues to rise at a rate of 13% (2006–2017) and that the requirements for work experience are substantially extended, diversity of job titles becomes prevalent, and rich service experience and continuous lifelong learning skills are becoming more and more predominant for librarians. This analytical investigation informs the emerging demands in the American job market debriefing the prioritization and reprioritization of the current core competency requirements for ALA librarians. © The Author(s) 2021.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Bridging digital divides during COVID-19: Findings from the 2020-2021 connecticut state library digital inclusion survey - Real, Brian (Public Library Quarterly, 2021)
This article presents findings from the 2020–2021 Connecticut State Library Digital Inclusion Survey. The primary purpose of this study was to determine what actions public libraries in Connecticut are already taking to meet the digital inclusion needs of their communities and what information and assistance they need to better meet these goals. However, since this study was launched during the COVID-19 pandemic, the author customized numerous questions to focus on how public libraries have adjusted their operations when patrons have had limited access to library buildings. Responses from public library representatives throughout the state show that libraries have used tactics such as delivering previously in-person public programs through video conferencing formats and shifting portions of their physical materials budget to support digital items. © 2021 The Author(s). Published with license by Taylor & Francis Group, LLC.
11 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Public library events: Who, what, where, when, and why? - Kukiolczynski, Katie Teresa; Liu, Yan Quan (Public Library Quarterly, 2021)
An explorative survey pertaining to organization and execution of programs and events offered in public libraries across Connecticut revealed that library programs have been steadily increasing in recent years, with most libraries providing one hundred or more programs a year. The types of programs that are most popular vary throughout the library’s open hours. Children’s programming appears to be more popular during the day while adult programming is more popular in the evening. Program popularity is based on grouping and continuous support from external partners. While this study confirmed that both library space and library staff sizes are adequate for programming, a further investigation would assert that this is the case within nationwide library programming.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103569958
Keywords: Connecticut; Public libraries; dept.ils; library events; library programs; peer-reviewed

Behind the transmitter: differences in archival practices between nonprofit and commercial radio stations - Falcone, Michael; Real, B.; Liu, Y. Q. (Journal of Archival Organization, 2020)
Many radio collections within the United States are maintained in more informal program libraries and archives in hundreds of geographically dispersed broadcasting stations throughout the country. To assess the full extent of this problem and real risk posed to station-owned radio collections, this article assesses the results of a survey administered across twenty-seven nonprofit and commercial stations or corporate parent companies. Nonprofit stations, its findings suggest, are more likely to actively maintain their archives and do so in a manner that shows awareness of current archival standards, whereas commercial stations are less likely to exert active stewardship over their collections. © 2020 The Author(s). Published with license by Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] tex.ids: falconeTransmitterDifferencesArchival2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086264842 type: Article
Keywords: Radio; audio preservation; college radio; dept.ils; peer-reviewed; radio archives; radio preservation

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed

Private life, public diplomacy: Tibor Hirsch and documentary filmmaking for the cold war USIA - Real, Brian (Historical Journal of Film, Radio and Television, 2020)
The United States Information Agency acted as a significant patron of American independent and nontheatrical filmmakers during the 1960s, commissioning short documentaries to carry positive messages about America to foreign audiences. While much of the existing scholarship on the USIA’s motion picture output focuses on works that address major policy issues such as the civil rights movement or that were made by directors who went on to have well-known careers, many of its films and directors have been forgotten. One such filmmaker is Tibor Hirsch, whose past as a refugee from the 1956 Hungarian Revolution influenced his films Transportation USA (1966) and Six Who Fled (1972). Hirsch’s earlier career as a photojournalist informed his work for the USIA, while the style he developed through making government films led directly into his later career as a highly successful television commercial director.
0 citations (Crossref) [2023-10-31] tex.ids: realPrivateLifePublic2019, realPrivateLifePublic2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85073924504 type: Article
Keywords: dept.ils; peer-reviewed